Fluid Therapy in COVID-19 Disease: Review - Esfandiar, Nasrin; Kompani, Farshid (Journal of Pediatric Nephrology, 2020)
COVID-19 pandemic due to the new corona virus 2019 is an important cause global problems. This infection begins with symptoms such as fever, cough, anorexia, malaise, sore throat, and can progress to acute respiratory disease syndrome (ARDS) and necessitating intensive care unit (ICU) admission with an estimated mortality rate of 3%. There is no confirmed specific antiviral treatment despite different treatment protocols. Supportive care especially fluid therapy plays a very important role in this disease. The aim of this review is to Institute effective strategies for effective fluid therapy in critically ill pediatric patients admitted to ICU. Keywords: COVID-19; Corona virus disease 2019; SARS-CoV-2; Fluids; Child; Intensive care.